Tax challenges arising from digitalisation. Analysis of the spanish Tax on Digital Services from an International and European perspective - Jabalera Rodríguez, Antonia (2021)
The pandemic caused by COVID 19 has accelerated the transition towards an even more digitized economy, and it has further evidenced the need for a new international regulation on a fairer allocation of tax rights for large companies that operate internationally and with a high profiability. While waiting for the recently adopted international agreement within the OECD/G20 Inclusive Framework on BEPS, to be signed, or a Digital Tax is approved in the European Union, Spain has joined the trend followed by other States, approving the Digital Services Tax. This Tax is being critized for its possible incompatibility with International Tax Law and European Law. In this work, we will analyze the essential elements of this tax, we will identify the main controversial issues that its legal regime raises from international and european law, and we will try to answer to them.